Design of Dexterous Hand for Massage and Its Position Analysis and Simulation - Zhou Runsheng; Yin Xiaoqin; Zhu Hejun (Jixie chuandong)
In order to improve the automation degree of the massage robot,the structure design and kinematics analysis of a four fingered,motor-driven robotic hand for massage robot is completed. Each finger has two joints: the first joint and the second joint. And the degree of freedom of the hand is four by connecting the first joints and second joints of index finger,middle finger and ring finger respectively. In addition,the crank-rocker mechanism is creatively adopted to driven the second joint,which is conducive not only to enhance the continuity and the periodicity of pinching manipulation,but to also avoid frequent reversing the rotation of motor,prolonging the service life of the motor. At last,to verify the design,the model of dexterous hand is developed. The rationality and feasibility of the mechanism of hand are proved by ADAMS motion simulation and MATLAB numerical analysis.